Elusive Recurrent Bacterial Contamination in a Diatom Culture: A Case Study - Alexey A. Morozov (MDPI AG, 2021)
In preparation for whole-genome sequencing, the axenic culture for two strains of a freshwater diatom Fragilaria radians were produced. Although their axenicity was controlled for the cultures’ entire lifetime, the published genomic assembly was later found to contain a large amount of bacterial sequences. Using various in silico analyses of whole genome read libraries and 16S rRNA sequencing of culture samples, we reconstruct the history of the contamination and document the failures of various axenicity control methods. This knowledge is used to discuss how these failures could have been avoided, and to provide guidelines for future works on axenic diatom cultures.